MODERN DIRECTIONS AND CURRENT PROBLEMS OF LINGUISTICS - Tursunov Jakhongir Aminovich (Research Parks Publishers, 2023)
This scientific article explores the contemporary landscape of linguistics, highlighting key directions and addressing current challenges in the field. Linguistics, as the scientific study of language, has evolved significantly over the years, reflecting advancements in technology, globalization, and interdisciplinary collaboration. This article aims to provide an overview of the modern directions shaping linguistics and the persistent challenges that researchers grapple with today. Linguistics, the scientific study of language, has witnessed significant transformations in recent years, propelled by advancements in technology, interdisciplinary collaborations, and a growing awareness of the dynamic nature of language. This article explores the modern directions and current problems in linguistics, delving into key areas such as computational linguistics, neurolinguistics, sociolinguistics, and the challenges posed by linguistic diversity and language endangerment. By addressing these issues, linguists aim to gain a deeper understanding of the complexities inherent in language and contribute to the broader field of cognitive science.